PENINGKATAN KOMPETENSI DIGITAL GURU DAN MAHASISWA MELALUI WORKSHOP "SERU DAN CERDAS! MENGUASAI PECAHAN DENGAN TIKTOK" - Rafika Riana Chn; Zulkardi Zulkardi; Yusuf Hartono; Ely Susanti (Jurnal Terapan Abdimas, 2025)
Abstract. Digital transformation in education requires teachers and student teachers to master technology skills as an innovative learning medium. The workshop Fun and Smart! Mastering Fractions with TikTok was held as part of a community service activity with the aim of improving participants digital competence in designing educational content based on social media. This activity used a service learning approach and was carried out online via Zoom and Google Classroom. A total of 207 participants, consisting of teachers and mathematics education students from various levels, attended the training session in the form of presentations, interactive discussions, and assignments to make fraction learning videos using the TikTok application. The results of the questionnaire showed a positive response from participants towards the implementation of the workshop. A total of 63.6% stated that the facilitator mastered the material well and created an interactive learning environment; 59.1% considered the material relevant and applicable in their work; and 50% felt more confident in applying the knowledge from the workshop. Although only 45.5% of participants considered that the workshop directly improved performance or that TikTok was effective for fraction learning, enthusiasm for this approach remained high. Overall, this workshop proved effective in increasing participants' understanding of the use of social media as a learning tool, as well as providing contextual, enjoyable, and relevant digital learning experiences. This activity strengthens the role of teachers and students as adaptive educators in the digital era.   Abstrak. Transformasi digital dalam pendidikan menuntut guru dan mahasiswa calon guru untuk menguasai keterampilan teknologi sebagai media pembelajaran yang inovatif. Workshop Seru dan Cerdas! Menguasai Pecahan dengan TikTok diselenggarakan sebagai bagian dari kegiatan pengabdian kepada masyarakat dengan tujuan meningkatkan kompetensi digital peserta dalam merancang konten edukatif berbasis media sosial. Kegiatan ini menggunakan pendekatan service learning dan dilaksanakan secara daring melalui Zoom dan Google Classroom. Sebanyak 207 peserta, terdiri dari guru dan mahasiswa pendidikan matematika dari berbagai jenjang, mengikuti sesi pelatihan berupa presentasi, diskusi interaktif, dan penugasan pembuatan video pembelajaran pecahan menggunakan aplikasi TikTok. Hasil kuesioner menunjukkan respons positif dari peserta terhadap pelaksanaan workshop. Sebanyak 63,6% menyatakan fasilitator menguasai materi dengan baik dan menciptakan lingkungan belajar yang interaktif; 59,1% menilai materi relevan dan dapat diterapkan dalam pekerjaan; serta 50% merasa lebih percaya diri dalam mengaplikasikan ilmu dari workshop. Meskipun hanya 45,5% peserta menilai bahwa workshop secara langsung meningkatkan kinerja atau bahwa TikTok efektif untuk pembelajaran pecahan, antusiasme terhadap pendekatan ini tetap tinggi. Secara keseluruhan, workshop ini terbukti efektif dalam meningkatkan pemahaman peserta terhadap pemanfaatan media sosial sebagai sarana pembelajaran, serta memberikan pengalaman belajar digital yang kontekstual, menyenangkan, dan relevan. Kegiatan ini memperkuat peran guru dan mahasiswa sebagai pendidik adaptif di era digital.